2014
DOI: 10.1038/ki.2013.341
|View full text |Cite
|
Sign up to set email alerts
|

Failed renoprotection by alternatively activated bone marrow macrophages is due to a proliferation-dependent phenotype switch in vivo

Abstract: Alternatively activated macrophages (M2) regulate immune responses and ex vivo polarized splenic M2 are able to ameliorate renal injury including models of renal disease, such as adriamycin nephropathy. Whether M2 derived from other organs have similar protective efficacy is unknown. Here, we report adoptively transferred bone marrow M2 macrophages did not improve renal function or reduce renal injury in adriamycin nephropathy, whereas splenic M2 macrophages were protective. Bone marrow and splenic M2 macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 57 publications
4
65
0
1
Order By: Relevance
“…Strong M1 polarizing ability does not suggest weak M2 functions (tissue remodeling, wound healing, and immune regulation capacity) in vivo. Despite a strong capacity to polarize to M1, SPMs manifested stronger wound healing and tissue remodeling abilities under the M2 state, compared with BMs that failed renoprotection due to a proliferation-dependent phenotypic switch in vivo (Cao et al, 2014). Therefore, the three types of macrophages have distinct characteristics regardless of their resting or polarizing states.…”
Section: Discussionmentioning
confidence: 99%
“…Strong M1 polarizing ability does not suggest weak M2 functions (tissue remodeling, wound healing, and immune regulation capacity) in vivo. Despite a strong capacity to polarize to M1, SPMs manifested stronger wound healing and tissue remodeling abilities under the M2 state, compared with BMs that failed renoprotection due to a proliferation-dependent phenotypic switch in vivo (Cao et al, 2014). Therefore, the three types of macrophages have distinct characteristics regardless of their resting or polarizing states.…”
Section: Discussionmentioning
confidence: 99%
“…Among potential strategies [21-23], macrophage cell-therapy provides promising but discordant results [12, 14, 15, 19, 20, 24]. Macrophage precursors can be isolated from the bone marrow or spleen, alternatively activated in vitro and then infused to test their effect on acute and chronic kidney disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies suggested that macrophages change their phenotype in response to signals from the local kidney milieu although the mechanisms by which they are polarized are not well understood [12, 13]. Ex vivo programmed macrophages displaying anti-inflammatory or reparative phenotype have been used as a macrophage cell therapy in distinct injured kidney mice models including IRI, lupus nephritis and Adriamycin nephropathy [12, 14, 15] with discordant results, suggesting thatphenotypic stability of transferred cells in vivo is critical to achieve therapeutic success.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10- and TGF-β-induced M2c macrophages have greater potency in decreasing renal damage and proteinuria, since M2c can induce the differentiation of immune-suppressing T regulatory cells through a B7-H4-dependent mechanism [17]. It is interesting that IL-10/TGF-β- or IL-4/IL-13-modified bone marrow-derived macrophages fail to protect against renal injury, because the anti-inflammatory phenotype of bone marrow-differentiated M2 cells is easily lost due to the capacity of continuous proliferation [50], which minimizes the clinical application of autologous macrophage-based therapy by modifying the bone marrow cells of patients.…”
Section: Macrophage-based or Targeted Therapy For Renal Diseasesmentioning
confidence: 99%